Diversity of Indigenous Fungi on the Roots of Eucalyptus deglupta in the Pelangi Forest at Ijen Geopark, Bondowoso - Hanizar, Evi; Imamah, Annisa Nur; Sari, Dwi Nur Rikhma (Biota, 2026)
Eucalyptus deglupta, a native tree species known for its ecological and economic value, forms unique associations with root fungi that play essential roles in nutrient cycling and plant health. Therefore, this study aims to explore the diversity of indigenous fungi associated with the roots of Eucalyptus deglupta in the Pelangi Forest, located within the Ijen Geopark area, Bondowoso Regency. The methods employed included the isolation of fungal cultures and subsequent identification through macroscopic and microscopic examination of morphological characteristics.  The isolation process yielded eight fungal isolates representing seven species: Microsporum gypseum, Aspergillus flavus, Mucor sp., Trichoderma sp., Geotrichum sp., Saccharomyces cerevisiae, and Cladophialophora sp. The results indicated a considerable diversity among the isolated fungal species, with several taxa being reported for the first time in the study areaThese findings provide a valuable baseline for future ecological, biotechnological, and conservation studies, particularly in exploring the potential roles of these indigenous fungi in forest health, ecosystem resilience, and sustainable land management practices.